2011
DOI: 10.1103/physrevlett.107.086602
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Ultrafast Dynamic Metallization of Dielectric Nanofilms by Strong Single-Cycle Optical Fields

Abstract: We predict a dynamic metallization effect where an ultrafast (single-cycle) optical pulse with a ≲1 V/Å field causes plasmonic metal-like behavior of a dielectric film with a few-nm thickness. This manifests itself in plasmonic oscillations of polarization and a significant population of the conduction band evolving on a ~1 fs time scale. These phenomena are due to a combination of both adiabatic (reversible) and diabatic (for practical purposes irreversible) pathways.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 20 publications
1
49
0
1
Order By: Relevance
“…7 (b). These transitions, which appear due to adiabatic population transfer, are analogous to those appearing due to metallization of dielectric nanofilms 11,13 .…”
Section: A Enhancement Of Reflection Of the Optical Pulsementioning
confidence: 99%
See 2 more Smart Citations
“…7 (b). These transitions, which appear due to adiabatic population transfer, are analogous to those appearing due to metallization of dielectric nanofilms 11,13 .…”
Section: A Enhancement Of Reflection Of the Optical Pulsementioning
confidence: 99%
“…This implies that in high fields the dielectric (silica) becomes much more polarizable ("softer") than expected from the low-field behavior. This softening is interpreted as a precursor to the adiabatic metallization 11,13 , which is incomplete because the present field is too fast to be adiabatic.…”
Section: A Enhancement Of Reflection Of the Optical Pulsementioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism relies on the effect of "adiabatic metallization", predicted theoretically for dielectric nanofilms [68,69]. It was found that a strong electric field can significantly and reversibly change the optical and electric properties of a sufficiently thin dielectric nanofilm.…”
Section: Adiabatic Metallizationmentioning
confidence: 99%
“…Related work with solids subjected to strong fields has also shown that the material may be reversibly changed from being a dielectric (insulator) to a semi-metal (conductor) in a femtosecond [9][10][11] .…”
mentioning
confidence: 99%